Simbol Dalam Relasi Sosial Antara Pedagang dan Pengunjung Pasar Terapung Lok Baintan - Mutiya, Hana; Hakim, Arif Rahman (Prodi Sosiologi FISIP ULM, 2024)
The symbols used by floating market traders are different from those used by market traders in general, such as the use of pantun, tanggui, and kakamban. This research aims to examine the meaning behind the symbols used by Lok Baintan floating market traders and their function in building social relations with visitors. This research uses social relations theory and symbolic interactionism theory. This research uses a qualitative approach with semiotic analysis. The research informants were traders and visitors of Lok Baintan floating market. Data were collected through observation, interviews and documentation, and analysed using two-stage meaning of signs, namely denotation and connotation (Roland Barthes' semiotic theory). The results showed that traders in Lok Baintan village are divided into two, namely home-based traders and floating market traders. There are symbols used by floating market traders to build social relations with visitors, namely using cold pupur, tanggui, colourful jukung, kakamban, negligee and brightly coloured clothes, tapih, baturai pantun and contracts in buying and selling. The denotation or original meaning of the use of cold pupur, tanggui, colourful jukung, kakamban, negligee and brightly coloured clothes, tapih, baturai pantun and buying and selling contracts was found. The connotation meaning is the use of cold pupur, tanggui, colourful jukung, kakamban, negligee and brightly coloured clothes, tapih, baturai pantun and buying and selling contracts. The myth is that the use of cold pupur is considered an attention-getter in order to quickly find a mate. Mutual interaction at the Lok Baintan Floating Market is a form of Social Relation that runs well. This research is able to analyse the meaning of two stages of signs regarding the interactions that occur in the Floating Market.